Rapid annotation and structural characterization of saponins in the active fraction of Albizia julibrissin by high‐performance liquid chromatography coupled with quadrupole time of flight mass spectrometry based on accurate mass database. Issue 18 (25th July 2019) - He, Yanfei; Ni, Tiantian; Liu, Zhaoying; Ye, Yiping; Sun, Hongxiang
Abstract: The purified active fraction of Albizia julibrissin saponin was proved to be a promising adjuvant candidate for vaccine. In this study, a simple, convenient, and practical strategy was established for characterizing the saponins in this purified active fraction. The personal accurate mass database including chemical structure, molecular formula, and theoretical mass was first constructed by collecting 110 reported known saponins from genus Albizia species. The raw data was obtained by high‐performance liquid chromatography coupled with quadrupole time of flight mass spectrometry. The potential compounds were extracted from raw data, and matched with the accurate mass databases. A series of saponin compounds were predicted and their chemical structures were characterized by interpreting the tandem mass spectrometry data. A total of 29 saponins including 10 new compounds and 5 first found saponins from A. julibrissin were successfully characterized in this purified active fraction using this new strategy.